Beginning Swift: Master the Fundamentals of Programming in Swift 4 - Kerr, Rob; Morstøl, Kåre (Packt Publishing, Limited, 2018)
Take your first foray into programming for Apple devices with Swift.Swift is fundamentally different from Objective-C, as it is a protocol-oriented language. While you can still write normal object-oriented code in Swift, it requires a new way of thinking to take advantage of its powerful features and a solid understanding of the basics to.